2023
DOI: 10.3389/fenrg.2022.989393
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced enzymolysis and bioethanol yield from tobacco stem waste based on mild synergistic pretreatment

Abstract: The use of mild pretreatment conditions can significantly lower the cost of the biorefining process. This study evaluated a mild pretreatment approach for tobacco stem waste using a combination of dilute acid and dilute alkali. By optimizing the pretreatment conditions, we obtained a high reducing sugar concentration at a pretreatment temperature <100°C. Increasing the acid or alkali strength in a single pretreatment step did not always improve the result; instead, the synergistic effect of both pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…The research on the bioconversion of lignocellulosic byproduct corn stover into the value-added fermentative product L-lactic acid using the furfural tolerant Enterococcus mundtii WX1 and Lactobacillus rhamnosus SCJ9 showed that corn stover pretreated with 1% (v/v) sulfuric acid was selected for L-LA fermentation and shows the highest efficacy of fermentable sugar with the optimal conditions achieved for the release of glucose and xylose at 24.5 g/L and 11.2 g/L, respectively, from 100 g/L pretreated corn stover at 121 • C for 30 min [102]. A similar result was presented by other researchers reported in the study of tobacco stem waste [103], palm kernel shell [104], sugarcane bagasse [105], and oil palm frond bagasse [106] that the dilute acid for chemical pretreatment is effective to attain high reactivity and generates protons that have a quick diffusion which substantially enhances the hydrolysis of amorphous cellulose chains and the solubilization of hemicellulose.…”
Section: Ethanol Synthesis Based On Lignocellulosic Materialssupporting
confidence: 76%
“…The research on the bioconversion of lignocellulosic byproduct corn stover into the value-added fermentative product L-lactic acid using the furfural tolerant Enterococcus mundtii WX1 and Lactobacillus rhamnosus SCJ9 showed that corn stover pretreated with 1% (v/v) sulfuric acid was selected for L-LA fermentation and shows the highest efficacy of fermentable sugar with the optimal conditions achieved for the release of glucose and xylose at 24.5 g/L and 11.2 g/L, respectively, from 100 g/L pretreated corn stover at 121 • C for 30 min [102]. A similar result was presented by other researchers reported in the study of tobacco stem waste [103], palm kernel shell [104], sugarcane bagasse [105], and oil palm frond bagasse [106] that the dilute acid for chemical pretreatment is effective to attain high reactivity and generates protons that have a quick diffusion which substantially enhances the hydrolysis of amorphous cellulose chains and the solubilization of hemicellulose.…”
Section: Ethanol Synthesis Based On Lignocellulosic Materialssupporting
confidence: 76%
“…The 2% NaOH treatment resulted in the highest glucose (368 mg/g of dry biomass) and xylose (64 mg/g of dry biomass) production during enzymatic hydrolysis, with glucan and xylan conversions of 50.6% and 32.2%, respectively [107], comparable to those observed in Bermuda grass pretreatment by [117]. However, increasing acid or alkali concentration alone does not always yield better results, but their synergistic effect is crucial [118].…”
Section: Morphology and Crystallinity Before And After Acidic And Alk...mentioning
confidence: 84%